Qualitative and quantitative study of hydroquinon in some skin whitening products available in local market - عبود آيات; حكيم رشا (Latakia University Journal -Medical Sciences Series, 2021)
Hydroquinone is one of the most effective skin lighteners in treating pigmentation. The FDA and the European Union allow to be used in pharmaceutical creams at concentrations of 2-4%, while its presence in creams that lighten the skin is prohibited due to its carcinogenic effects. This study aimed to qualitative and quantitative determination of hydroquinone in cosmetic whitening creams. Quantitative investigation was carried out using colorimetric methods, thin layer chromatography, and UV/visible spectroscopy. UV-Visible spectroscopy was also used for quantitative purposes. The method was firstly validated, and then applied to the studied samples. The results of hydroquinone quantitative determination in the studied skin whitening creams showed the presence of hydroquinone in 6 types of its three patches, although the manufacturers of the six preparations did not indicate the presence of hydroquinone. Its concentration in two preparations were less than 2%, and in two preparations between 2 and 4%, while its concentration in the two preparations exceeded 4%.